2021
DOI: 10.26848/rbgf.v14.3.p1675-1689
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de Secas e Antropização na Dinâmica da Cobertura Florestal em Fragmento do Domínio Fitogeográfico da Caatinga

Abstract: Este trabalho objetivou avaliar a influência da antropização e de secas severas na dinâmica da cobertura florestal de um fragmento de caatinga na região semiárida do Brasil, ao longo de 32 anos. Para o cálculo do índice de seca, agrupou-se os valores de precipitação média pondera           da anual da série histórica (1988 - 2019) em Decis. A partir do quantitativo de área encontrada nas classes de uso e ocupação (cobertura florestal conservada, cobertura natural campestre, área antropizada e corpos d’água) do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…According to Aquino et al (2021), the fact that severe drought phenomena occur regularly in this semiarid region aggravates the impacts on the dynamics of regeneration on the forest cover in caatinga fragments, making this process slower.…”
Section: Discussionmentioning
confidence: 99%
“…According to Aquino et al (2021), the fact that severe drought phenomena occur regularly in this semiarid region aggravates the impacts on the dynamics of regeneration on the forest cover in caatinga fragments, making this process slower.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural and cattle ranching activities and climate variations have a determining influence on forest cover dynamics and represent the most studied factors (Aquino, Rocha Neto, Moreira, Teixeira, & Andrade, 2018;Aquino, Andrade, Filho, & Campos, 2021;Grau, Gasparri, & Aide, 2005;Schulz, Cayuela, Echeverria, Salas, & Benayas, 2010). In the municipality of Tauá, in the state of Ceará, Brazil, in years with rainfall above the historical average, there was a significant increase in degraded areas, resulting from the advance of land incorporated into subsistence agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the dynamics of land cover and land use in the municipality of Quixadá, Ceará State, Brazil, Aquino et al (2021) found that in years of severe drought, there was a decrease in conserved Caatinga and growth of disturbed areas, with modification of the herbaceous and shrub strata. For these authors, rainfall does not have as much influence on vegetation dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The Caatinga ecogeographic domain is exclusive to the Brazilian territory, predominantly in the northeast region of the country, and represents about 13% of the national territory, occupying an area of 912,000 km2 rich in biodiversity (BARROS et al, 2021). The main characteristic of Caatinga environment is the poorly developed soils, with an intense dry period, with almost no rain for 8 to 10 months throughout the year (AQUINO et al, 2021). Due to anthropogenic exploration as well as the edaphoclimatic characteristics of the semi-arid region, the Caatinga is in a condition of vulnerability, highly threatened in the scenario of rising global temperatures, putting this region on alert (NOBRE, 2011) due to the risks of desertification and salinization of soils (OLIVEIRA et al, 2013;NOBRE, 2011).…”
Section: Introductionmentioning
confidence: 99%